2020
DOI: 10.1007/s12371-020-00456-5
|View full text |Cite
|
Sign up to set email alerts
|

Inventory and Quantitative Assessment of Geosites in Rabat-Tiflet Region (North Western Morocco): Preliminary Study to Evaluate the Potential of the Area to Become a Geopark

Abstract: The Rabat-Tiflet area (north-western Morocco) has a complex geological setting and a high geodiversity, two reasons that justify the geoheritage inventory done in this work. The inventoried 13 geosites were quantitatively assessed and clearly show that the Tortonian/Messinian Akrech River GSSP Stratotype is the most important geosite in the area due to its high international scientific value. In addition, the majority of the other geosites are characterized by moderate scientific, educational, and touristic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…The findings are in line with previous studies [66][67][68][69][70][71] that have reported that the attitudes of the local community in different regions often differ from the opinions of experts and/or visitors in regard to the importance of examined geosites, which is the reason why it is essential to take into account the overall public opinion in geotourism development. This equally applies to the locals who live near the geosite [66,67], but also to members of local authorities and municipal governments who can legally encourage and support the development of sustainable geotourism and the affirmation of the geosite [68][69][70][71].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings are in line with previous studies [66][67][68][69][70][71] that have reported that the attitudes of the local community in different regions often differ from the opinions of experts and/or visitors in regard to the importance of examined geosites, which is the reason why it is essential to take into account the overall public opinion in geotourism development. This equally applies to the locals who live near the geosite [66,67], but also to members of local authorities and municipal governments who can legally encourage and support the development of sustainable geotourism and the affirmation of the geosite [68][69][70][71].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the newly suggested M-GAM-2 model includes the role of the local government/authorities. This addition to the existing models is justified by the findings of several modern studies [68][69][70][71], which have proved a great importance of the local authorities in the protection and promotion of geoheritage sites.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this methodology has already been employed in the other points assessment of geological interest in Ecuador (e.g., [8,26,[77][78][79][80][81][82]). In general, the work carried out in the study area regarding the inventory, valuation, promotion, protection and use of geosites is similar to the approach adopted in other countries (e.g., [71,[83][84][85][86][87][88][89][90]).…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 99%
“…Over the past decade, there has been a notable increase in the number of studies focused on geoheritage evaluation in arid environments, particularly in the MENA (Middle East-North Africa) region. This surge is especially evident in countries such as Iran [11,[38][39][40][41][42][43][44][45][46][47][48][49][50], Egypt [24,[51][52][53][54][55][56][57][58][59] and Morocco [60][61][62][63][64][65][66][67]. The majority of these investigations involve inventories or inventory-based evaluations, which correspond to the initial stages of geoheritage conservation proposed by Brilha [9].…”
Section: (C) Geoheritage Evaluation In Arid Environmentsmentioning
confidence: 99%